(untitled) (Colombia Medica, 2016)
Case Description:An 82-years old Hispanic woman with a past medical history significant for pulmonary thromboembolism on oral anticoagulation, rheumatoid arthritis, and hypertension developed a new onset thrombocytopenia. Clinical Findings: Small clonal B-cells populations (SCBP) also known as monoclonal B-cell lymphocytosis was found as part of the workup for an idiopathic thrombocytopenia and lead ultimately to the diagnosis of parotid primary follicular lymphoma coexisting with Warthin tumor involving the bone marrow in a small extent and oncocytic papilloma located in the maxillary sinus. Treatment and Outcome: Patient was treated with Rituximab monotherapy with improvement on her platelet count. Clinical relevance: Although it is unclear the role of this clonal cells, they may work as a possible diagnostic tool for occult lymphomas. Further prospective studies are needed to confirm this possible association.